Analisis Kesiapan Guru dalam Implementasi Kurikulum Merdeka Belajar di SDN 02 Kuwaron Gubug Grobogan - Maulidia, Elma; Attalina, Syaili Nichla Choirin (Journal Prakarsa Paedagogia, 2024)
The Merdeka Curriculum is a curriculum with a variety of intracurricular learning models where the content will be more optimal so that students have enough time to explore concepts and strengthen competencies. Teachers have the freedom to choose various teaching tools so that learning can be tailored to the learning needs and interests of students. The problems faced by teachers related to the implementation of the Independent Learning Curriculum are that there are many components that require readiness for teachers to apply the independent curriculum, including lack of experience with independent learning, lack of references, uneven access to learning and time management. . The aim of this research is to qualitatively analyze teacher readiness in implementing the Independent Learning Curriculum. The method used in writing this article uses a descriptive-qualitative method. In this research, the author focuses on problems based on facts which are carried out by observation, interviews, and studying available documents with the assistance of the Class Teacher. The results of the research show that in terms of teacher administration, the implementation of the independent learning curriculum is based on the availability of documents which include books, teaching modules, step learning objectives, annual programs, semester programs, educational calendars and details of effective weeks at SDN 02 Kuwaron Gubug Grobogan, which are already available. Completely so that in general they are ready to apply the Independent Learning Curriculum.